(untitled) (Research, Society and Development, 2020)
Assistance to students with special learning needs requires understanding the individual as a unique being, immersed in a physical and social environment, with different characteristics and needs. In this sense, studies aimed at understanding and developing strategies to meet special needs, including high abilities or giftedness, are imminent. Thus, this research aimed, through bibliographic reviews in scientific journals, works and legal documents that guide special education in the country, the understanding of high abilities / giftedness under the empirical and scientific view, converging on the pointing of essential factors that make the school is a relevant space in welcoming the student with this special learning need. Among the results, it can be seen that, under an empirical view, different representations about high abilities are associated with the idea of geniuses, which converges in the emergence of naive or mistaken conceptions. Scientifically speaking, the skilled are characterized as people who show remarkable performance, talent or superior skills in one or several areas. Taking education as an ally to the process of understanding, identification and assistance is essential for this group to develop their talents, in a free and coherent way, with a view to building a comprehensively plural society. The main contribution of this work is to provide the means for an introductory reflection about attending students with high skills in the school context.